CIVIL SERVANTS 'COMPETENCE AS PUBLIC SERVICES - M. Fikro Rusdi; Jeane Langkai; Charles H S Tangkau (SEIKO : Journal of Management & Business, 2020)
This study aims to describe the analysis, and interpret the Competencies of Civil Servants in carrying out governmental duties as a public service at the Bolaang Mongondow Utara Regency Secretariat. This type of research is Qualitative with a case study approach. The results showed that: The implementation of competency standards for Civil Servants in carrying out government duties as a public service at the Regional Secretariat of North Bolaang Mongondow Regency has not run as expected. This can be seen from the results data (1) the processes and procedures carried out have not fully met the process in accordance with the guidelines for rolling position in North Bolaang Mongondow Regency which is in accordance with the Minister of Administrative Reform and Bureaucracy Reform (PERMENPANRB) Number 38 of 2017 concerning Position Competency Standards State Civil Apparatus. (2). The procedure for rolling has already been stated in the Regent's decree, but the process is not yet understood and follows the stages and indicators that must be met that have not gone well as expected. (3). in the placement process there are officials who are not in accordance with their competencies to occupy the position because if viewed from the rules not in accordance with the guidelines the Managerial Competency indicator is measured from the level of education, structural training or management, and leadership experience this is contained in PP 11/2017 Article 55. ( 4) employee qualifications although it is recognized that the fulfillment of qualifications and competencies is still around 60% -70% according to the requirements. (5) meryt system is also not fully implemented, the quality factor of HR (Human Resources) seen from the level of education still needs to be improved especially at the S2 level , and the level of skills of employees who must follow Diklatpim according to the level of position they occupy must be appropriate and get attention. Keywords: Public Policy, Public Services, PNS Competence